Fiziologija rastlin: Priročnik z navodili za vaje - Ambrožič-Dolinšek, Jana; Ciringer, Terezija (2022)
Plants Physiology: Exercise Instructions Manual. The manual is prepared for students in undergraduate courses in biology, ecology with nature conservation, and prospective biology teachers who wish to become familiar with experimental work in plant physiology. It consists of eight sections dealing with plant pigments, plant respiration and photosynthesis, plant enzyme activity, plant water regulation, plasmolysis, plant mineral nutrition by recognizing symptoms of nutrient deficiency, methods for determining sugar content, and bioassays for plant hormones. Each of the exercises begins with a content introduction and continues with the objectives, tasks, materials, and procedure for the exercise. The exercises are supported by pictures of the individual experiments, tables, chemical formulas for calculating individual physiological parameters, and instructions for using chemicals and equipment.
Keywords: experimental exercises; manual, plant physiology; plant biology; laboratory apparatus and procedures; laboratory plants